Comparative Analysis of ICO, DAOICO, IEO and STO. Case Study - A. S. Myalo (Финансы: теория и практика)
The article examines the problem of the ICO (Initial Coin Offering, from English — “initial offer of coins, initial placement of coins”). The information source is the ICO rating data of the return on investment in blockchain startups. The methodological base of the research is a situational comparative analysis of the ICO, DAOICO, IEO and STO and systematization of information. The author analyzes three new ICO models. The first one includes elements of Decentralized Autonomous Organizations (DAO). Its aim is to minimize the difficulties and risks associated with the ICO. The second model (Initial Exchange Offering (IEO), from English — “primary exchange offer”) is designed to minimize risks, liquidity problems and a delay in listing tokens at the end of the token sale. The third model — the Security Token Offering (STO, from English — “offer of security token”) — was designed to support real assets and comply with the SEC requirements. These models are a new direction for small and medium enterprises and investors. The absence of any scientific work emphasizes the relevance and scientific novelty of the study. The article is a follow-up of the empirical work related to the success of the ICO, as well as the basis for its revision using the case study results.